Tattoo removal with ingenol mebutate - Cozzi SJ; Le TT; Ogbourne SM; James C; Suhrbier A (Dove Medical Press, 2017)
Sarah-Jane Cozzi,1 Thuy T Le,1 Steven M Ogbourne,2 Cini James,1 Andreas Suhrbier1 1Inflammation Biology Laboratory, QIMR Berghofer Medical Research Institute, Brisbane, 2Genecology Research Center, Faculty of Science, Health, Engineering and Education, University of the Sunshine Coast, Maroochydore DC, QLD, Australia Abstract: An increasing number of people are getting tattoos; however, many regret the decision and seek their removal. Lasers are currently the most commonly used method for tattoo removal; however, treatment can be lengthy, costly, and sometimes ineffective, especially for certain colors. Ingenol mebutate is a licensed topical treatment for actinic keratoses. Here, we demonstrate that two applications of 0.1% ingenol mebutate can efficiently and consistently remove 2-week-old tattoos from SKH/hr hairless mice. Treatment was associated with relocation of tattoo microspheres from the dermis into the posttreatment eschar. The skin lesion resolved about 20 days after treatment initiation, with some cicatrix formation evident. The implications for using ingenol mebutate for tattoo removal in humans are discussed. Keywords: tattoo, ingenol mebutate, mouse